Nutritional strategies to minimize fatigue during prolonged exercise: Fluid, electrolyte and energy replacement - Dennis, S. C.; Noakes, T. D.; Hawley, J. A. (Journal of Sports Sciences, 1997)
While the presence of palatable (20 mmol l-1) concentrations of NaCl in drinks containing carbohydrate consumed during intense exercise would not be expected to promote absorption or significantly help maintain fluid balance, there is no doubt that athletes should ingest some form of carbohydrate (other than fructose) during moderate-intensity exercise lasting >90 min. As only ~20 g of ingested carbohydrate is oxidized in the first hour of exercise, athletes should probably consume 100 ml every 10 min of a dilute (3-5 g 100 ml-1) carbohydrate solution and thereafter increase the carbohydrate concentration to ~10 g 100 ml-1 to match the peak (~1 g min-1) ratesof plasma glucose oxidation. Drinking more than those amounts of carbohydrate may increase muscle glycogen oxidation by attenuating the fall in plasma insulin concentration and thereby delaying fat mobilization, especially at relatively low (55% of peak oxygen consumption) intensity exercise. As carbohydrate ingestion does not slow the rate of glycogen utilization in working muscle, it is also advisable for endurance athletes to start exercise with an adequate supply of muscle glycogen, irrespective of whether or not they ingest carbohydrate during exercise. While carbohydrate ingestion 'spares' conversion of liver glycogen to plasma glucose and prevents hypoglycaemia, it does not delay the fatigue associated with a low (~20 mmol kg-1) glycogen content in working muscle. Conversely, increases in glycogen content of working muscle at the start of exercise have no effect on the rates of plasma glucose oxidation. Higher initial rates of glycogen utilization by active muscles in 'carbohydrate-loaded' subjects decrease the indirect oxidation (via lactate) of non-working muscle glycogen, ratherthan the conversion of liver glycogen to plasma glucose. Hence, athletes should ingest carbohydrate during endurance exercise even if they have 'carbohydrate-loaded' before exercise.